Assessment of Factors Influencing the Implementation of Biosecurity Measures on Pig Farms in the Western Highlands of Cameroon (Central Africa) - Marc K. Kouam; Junior O. Moussala (Veterinary Medicine International)
Biosecurity plays an irreplaceable role in preventing diseases and increasing productivity on farm. The main objective of this study was to characterize pig farming and investigate factors influencing biosecurity on pig farms in the western highlands of Cameroon. Data were collected from May to July 2017 using a questionnaire and observations. A technical scoring system was developed from the biosecurity measures. The results revealed that most farmers are males (76.29%), on average 47.82 ± 10.34 years old, with secondary school level (53.61%). The most common husbandry system is extensive (73.22%). Over a total score of 93, measures with higher scores (>80) included “employees do not rear pigs at home,” “animals of different age not in the same room,” “unsold animals from market quarantined prior to reintroduction into the herd,” “production materials not exchanged among farms,” “piggeries clean every day,” “disinfectants used,” “pigs vaccinated,” and “vaccination calendar respected.” Those with the lowest score (<6) were “sanitary lock present,” “use of herd specific clean coveralls and boots on farm,” and “entry restriction sign post present.” The biosecurity level was associated with production system, with the score 6.57 and 3.66 points lower for extensive and semi-intensive farms, respectively, than for intensive system. Farmer’s age, gender, education level, and herd size did not affect the level of biosecurity. The results can be used to improve the general biosecurity status in pig herds in the country which in turn will lead, as observed elsewhere, to improved technical performance and economic gain.